1995
DOI: 10.1093/oxfordjournals.annonc.a059185
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent for phase I studies: Evaluation of quantity and quality of information provided to patients

Abstract: The informed consent procedure applied was satisfactory from a quantitative point of view, and the main items of information were acceptable to the patients. Meerweins's model proved to be applicable and useful for identifying pitfalls in communication. Greater attention should be paid to the indirect messages and implied criticisms of the patients to improve their participation in decision making. Physicians should become more skillful in providing adequate information and improve their methods of communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 26 publications
0
48
0
Order By: Relevance
“…A paper by Tomamichel et al [26] provides an objective report of investigator communication and the ICP of P1 trials. Analysis indicated that in more than half of the 32 taped consultations, the investigator scored on the lower half of the scale in terms of assessing patient understanding at the end of the consultation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A paper by Tomamichel et al [26] provides an objective report of investigator communication and the ICP of P1 trials. Analysis indicated that in more than half of the 32 taped consultations, the investigator scored on the lower half of the scale in terms of assessing patient understanding at the end of the consultation.…”
Section: Resultsmentioning
confidence: 99%
“…Of concern is Tomamichel et al's [26] report that only 11 of 32 taped consultations advised of the possibility of study withdrawal or treatment refusal. An analysis of 272 consent forms [23] found only 65% of consent forms mentioned the alternative of receiving no treatment, and only 56% mentioned supportive or palliative care as an alternative.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] A particular concern is that some patients do not have the requisite skill, numeracy, to understand and manipulate quantitative information about uncertain outcomes. For example, in a study of highly educated adults, Lipkus et al 12 found low levels of numeracy, with no more than one-third of respondents able to answer all 10 items correctly on the authors' numeracy scale.…”
mentioning
confidence: 99%
“…Although almost all investigators and institutional review boards agree as to the importance of informed consent (Kodish et al, 1992) and the guiding concept in ethical clinical research is informed consent, which is meant to guarantee the voluntary Received 31 May 1996 Revised 25 November 1996 Accepted 11 December 1996 Correspondence to: K Itoh nature of participation in clinical trials, there have been only a few reports from the viewpoint of the patients in phase I clinical trials of anti-cancer agents (Rodenhuis et al, 1984;Tomamichel et al, 1995;Daugherty et al, 1995). Furthermore, it is of interest to learn whether the patients' perception of these studies in Japan differs from that of patients in the United States and Europe.…”
mentioning
confidence: 99%